BUNGA RAMPAI KEBIJAKAN MENTERI KEUANGAN PURBAYA YUDHI SADEWA DENGAN REKOMENDASI KEBIJAKAN PENGEMBANGAN UMKM: STUDI KASUS SULAWESI UTARA - Yoan Purnamasari Makapuase Bahalau (JURNAL ILMIAH EDUNOMIKA, 2026)
This study examines the fiscal and financial policies of Indonesian Minister of Finance Purbaya Yudhi Sadewa (inaugurated September 8, 2025) and their relevance to the development of Micro, Small, and Medium Enterprises (MSMEs) in North Sulawesi Province. Using a qualitative descriptive approach with literature study and policy analysis methods, this research identifies four main policy instruments: (1) Rp200 trillion liquidity injection into state-owned banks; (2) 0.5% Final Income Tax incentive for MSMEs; (3) transformation plan of PNM into a National MSME Bank; and (4) implementation of Law No. 4/2023 on Financial Sector Development and Strengthening (UU P2SK) and OJK MSME Regulation. Findings show that while North Sulawesi recorded 37.6% MSME growth (from 44,308 units in 2022 to 60,961 units in 2023) and 5.39% economic growth throughout 2024, the transmission of central fiscal policy still faces structural barriers including digital divide between urban and remote island areas, low financial literacy, and fintech concentration in Java. This study recommends accelerating an inclusive digital financial ecosystem based on archipelago characteristics, strengthening regional banking intermediation, and improving MSME digital literacy as prerequisites for the effectiveness of Minister Purbaya's policies in North Sulawesi. Keywords : Fiscal Policy; Minister Purbaya; MSME ; Noerth Sulawesi; Digital Finance; Finance Inclusion